Safety of endovascular therapy for symptomatic intracranial artery stenosis: a national prospective registry. Issue 2 (12th October 2021) - Wang, Yabing; Wang, Tao; Dmytriw, Adam Andrew; Yang, Kun; Jiao, Liqun; Shi, Huaizhang; Lu, Jie; Li, Tianxiao; Huang, Yujie; Zhao, Zhenwei; Wu, Wei; Wan, Jieqing; et al.
Abstract : Introduction: The safety outcomes of endovascular therapy for intracranial artery stenosis in a real-world stetting are largely unknown. The Clinical Registration Trial of Intracranial Stenting for Patients with Symptomatic Intracranial Artery Stenosis (CRTICAS) was a prospective, multicentre, real-world registry designed to assess these outcomes and the impact of centre experience. Methods: 1140 severe, symptomatic intracranial arterial stenosis (ICAS) patients treated with endovascular therapy were included from 26 centres, further divided into three groups according to the annual centre volume of intracranial angioplasty and stent placement procedures over 2 years: (1) high volume for ≥25 cases/year; (2) moderate volume for 10–25 cases/year and (3) low volume for <10 cases/year. Results: The rate of 30-day stroke, transient ischaemic attack or death was 9.7% (111), with 5.4%, 21.1% and 9.7% in high-volume, moderate-volume and low-volume centres, respectively (p<0.05). Multivariable logistic regression confirmed high-volume centres had a significantly lower primary endpoint compared with moderate-volume centres (OR=0.187, 95% CI: 0.056 to 0.627; p≤0.0001), while moderate-volume and low-volume centres showed no significant difference (p=0.8456). Conclusion: Compared with the preceding randomised controlled trials, this real-world, prospective, multicentre registry shows a lower complication rate of endovascular treatment for symptomatic ICAS. Non-uniform utilisation in endovascular technology, institutional experience and patient selection in different volumes of centres may have an impact on overall safety of this treatment.